Factors influencing the outcomes of contrast-enhanced ultrasound in the detection of sentinel lymph nodes in breast cancer - Luo, Jun; Luo, Yunhao; Cao, Wenbin; Feng, Liting; Li, Chaonan; Liu, Yuyan; Huang, Dayan; Guan, Cheng; Lu, Qiang (Frontiers in Oncology, 2025)
ObjectiveTo analyze the influencing factors on the failure of sentinel lymph node (SLN) imaging in breast cancer by percutaneous injection contrast-enhanced ultrasound (CEUS).MethodsClinical data including basic characteristics, medical history, ultrasound technical parameters, and laboratory findings were collected from the patients, and the pathological results of sentinel lymph node biopsy (SLNB) were used as the gold standard for all patients. Logistic regression was used to analyze all influencing factors. The performance of the model was assessed using the area under the receiver operating characteristic curve (AUC), P<0.05 was statistically significant. Nomogram was developed for the assessment of risk prediction.ResultsA total of 1356 patients were included, of which 92.48% (1254/1356) had successful imaging and 7.52% (102/1356) had failed imaging. Logistic regression analysis showed that the quadrant location of tumor [(OR = 1.54, 95%CI: 1.01, 2.36)], the history of previous breast surgery [(OR = 3.05, 95%CI: 1.62, 5.72)], the metastasis of SLN [(OR = 2.68, 95%CI: 1.72, 4.15)], the history of neoadjuvant therapy [(OR = 2.90, 95% CI: 1.57, 5.37)], and the clinical prognostic stage [(OR = 3.50, 95% CI: 1.70, 7.22)] were the independent influencing factors of CEUS failure, with a statistically significant difference (P<0.05). The AUC of its predictive model in the training set was 0.72 (95% CI: 0.65-0.78), and the AUC of the predictive model in the validation set was 0.71 (95% CI: 0.61-0.81).ConclusionsThe quadrant location of tumor, the history of previous breast surgery, the metastasis of SLN, the clinical prognostic stage and the history of previous neoadjuvant therapy were the independent influencing factors for the failure of CEUS for SLN imaging in breast cancer.